Active tuberculosis detection by pouched rats in 2014: More than 2, 000 new patients found in two countries. Issue 1 (8th October 2016) - Poling, Alan; Valverde, Emilio; Beyene, Negussie; Mulder, Christiaan; Cox, Christophe; Mgode, Georgies; Edwards, Timothy L.
Abstract : Tuberculosis (TB) is a major problem in poor countries because sensitive diagnostic tools are unavailable. In 2014, our pouched rats evaluated sputum from 21, 600 Tanzanians and 9, 048 Mozambicans whose sputum had previously been evaluated by microscopy, the standard diagnostic for TB. Evaluation by the rats revealed 1, 412 new patients with active TB in Tanzania and 645 new patients in Mozambique, increases of 39% and 53%, respectively, when compared to detections by microscopy alone. These results provide further support for the applied use of scent‐detecting rats.